Reflexões sobre a Educação a Distância: o papel do professor tutor na perspectiva da mediação pedagógicaReflections about Distance Education - the role of the teacher-tutor in the perspective of pedagogic mediation (Revista Linhas, 2007)
Baseado na prática pedagógica de tutoria vivenciada pela autora, este artigo constitui pequena síntese retrospectiva da EaD como modalidade de ensino no mundo e no Brasil, ressaltando a experiência da UDESC. A abordagem dessa temática permeia a reflexão dos seguintes aspectos, essenciais para esse estudo: a utilização de material impresso, video, site na Internet , tele conferências, e-mail, telefone, encontros presenciais, materiais auto-instrucional, e a avaliação. Envolve, portanto, os aspectos metodológicos e teóricos que constituem a complexa função tutorial do professor em EaD.PALAVRAS-CHAVE: Educação a Distância. Professor-Tutor. Mediação Pedagógica.  This article reflects upon Distance Education and highlights the role of the teacher-tutor from the perspective of Pedagogical Mediation in this educational mode at the State University of Santa Catarina – UDESC. The paper is based on the author’s pedagogical experience as a tutor. It also includes a short retrospective synthesis of this educational mode in Brazil and throughout the world, emphasizing the experience at UDESC. The approach to this theme permeates the reflection of the following factors that are essential to this study: the use of printed materials, video, Internet sites, tele-conferencing, e-mail, telephone, personal meetings, instructional manuals and evaluation. It therefore involves the methodological and theoretical factors that constitute the complex tutorial function of the teacher in Distance Education.KEYWORDS: Distance Education. Teacher-tutor. Pedagogic Mediation.